Attitude determination system of nano-satellite - Chia, Jiun Wei (2017)
In recent years, the industry of miniature satellite based on cubesat standard has been growing rapidly. This growing industry has changed the direction of miniature satellite from educational and research purposes to application focused. As most of the implemented applications require target pointing, precise attitude determination is highly crucial to the mission success.